الجريدة الرسمية العدد 46 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 3392 لسنة 2024 -- قرار رقم 3505 لسنة 2024 -- قرار رقم 3507 لسنة 2024 -- قرار رقم 3508 لسنة 2024 --